Evaluasi Kualitas Fungsional Aplikasi POS Alfamart dari Repository GitHub Menggunakan Standar Pengujian ISO/IEC 29119 - Muhammad Ishomi Dhiwa; Sahala Yudha; Chairul Anwar (Journal of Information Systems and Business Technology, 2025)
The utilization of open-source software from public repositories often lacks standardized quality assurance and testing documentation, posing potential functional failure risks during operational deployment. This study aims to evaluate the functional quality and technical feasibility of the "POS Alfa" application sourced from the depthgilang GitHub repository, strictly adhering to the ISO/IEC 29119 international standard. Employing a Black Box Testing approach, the research methodology commenced with acquiring the source code to a local server, formulating a Test Plan, and designing test scenarios using Equivalence Partitioning and Boundary Value Analysis techniques to validate the system's business logic. The execution of 25 Test Cases revealed that while the basic system architecture functioned correctly, critical defects were identified within the input validation and user session management modules, which posed risks to data integrity. Following defect remediation simulation and re-testing, the success rate of the test scenarios improved significantly, leading to the conclusion that ISO/IEC 29119-based quality audits are essential for ensuring the stability of third-party source code before it is declared production-ready.